Penanaman Nilai-Nilai Kristen Berdasarkan Ulangan 6:7 bagi Pertumbuhan Manusia Rohani Anak - Samly, Deny; Saptono, Yohanes Joko (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2022)
Children's spiritual growth is significant for parents to pay attention to, and it is a task given by God to parents to become the main teacher for children's spiritual growth. This article explains the cultivation of Christian values based on Deuteronomy 6:7 for children's spiritual growth. Deuteronomy 6:7 states that God commands that parents carry this responsibility wholeheartedly to teach the diligent cultivation of Christian values, namely to give them in upbringing to children repeatedly. The thing instilled in the child is the most important and foremost to love God with all his heart, as stated in the previous verse (Deuteronomy 6:4-9). The cultivation of values to live produces the fruit of the spirit in their lives, and it is certainly the role of the work of the Holy Spirit that guides their lives. Every instillation of value given by parents to children that is carried out repeatedly will the child remember and apply it in their lives. Through this, they will also experience spiritual growth that loves God and makes God's words the foundation and principle of their lives. AbstrakPetumbuhan rohani anak sangat penting untuk diperhatikan orang tua dan adalah sebuag tugas yang diberikan oleh Tuhan kepada orang tua untuk menjadi guru utama bagi pertumbuhan kerohanian anak. Penulisan artikel ini bertujuan untuk menjelaskan tentang penanaman nilai-nilai Kristen yang berdasarkan pada Ulangan 6:7 bagi pertumbuhan rohani anak. Ulangan 6:7 menyatakan bahwa Tuhan memerintahkan agar orang tua membawa tanggung jawab ini dengan sepenuh hati untuk mengajarkan penanaman nilai Kristen dengan tekun yaitu memberikannya dalam didikan kepada anak secara berulang-ulang. Hal yang ditanamkan kepada anak yang terpenting dan terutama untuk mengasihi Allah dengan segenap hati seperti yang dinyatakan dalam ayat sebelum-sebelumnya (Ul 6:4-9). Penanaman nilai-nilai melainkan untuk hidup menghasilkan buah roh dalam hidup mereka dan sudah pasti adalah adanya peran karya dari Roh Kudus yang membimbing hidup mereka. Setiap penanaman nilai yang diberikan oleh orang tua kepada anak yang dilakukan secara berulang-ulang akan anak ingat dan mengaplikasikannya dalam kehidupan mereka. Melalui hal ini juga mereka akan mengalami pertumbuhan rohani yang mengasihi Tuhan dan menjadikan firman Tuhan sebagai pondasi serta prinsip dalam kehidulpan mereka.